2016
DOI: 10.1002/etc.3426
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and cellular responses of oysters (Crassostrea hongkongensis) in a multimetal‐contaminated estuary

Abstract: The Pearl River estuary, southern China, suffers from multiple sources of metal contamination as a result of the rapid industrial development in the region; but the biological impacts of contamination remain unknown. In the present study, a euryhaline oyster, Crassostrea hongkongensis, was collected from different sites of the Pearl River estuary; and various physiological (heart rate, alkaline phosphatase as homeostatic regulation, and glycogen as energy reserve) and cytological (lysosomal membrane stability)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…The sites had been exposed to different types and levels of metal pollution. Site 1, located near Shenzhen Airport, was the most heavily contaminated, whereas site 3, located in Lau Fau Shan, was the least metal contaminated . The concentrations of organic pollutants in the oysters of the Pearl River Estuary were reported to be at low levels .…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…The sites had been exposed to different types and levels of metal pollution. Site 1, located near Shenzhen Airport, was the most heavily contaminated, whereas site 3, located in Lau Fau Shan, was the least metal contaminated . The concentrations of organic pollutants in the oysters of the Pearl River Estuary were reported to be at low levels .…”
Section: Methodsmentioning
confidence: 97%
“…Previous studies have reported that C. hongkongensis have survived in some metal‐polluted estuaries of Southern China with extremely high metal levels in their bodies . In the companion study, we quantified the metal burdens in oyster tissues and found that the total Cu and Zn contents could reach up to 2.0% of oyster dry weights, even though the dissolved labile Cu and Zn concentrations were not high in waters of sampling sites . Such high concentration of metals in tissues may impact the antioxidant and detoxification systems of oysters, which play important roles in defending metal stresses by deleting reactive oxygen species (ROS) and detoxifying toxic metals.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations